Clinical PET-CT in Radiology Integrated Imaging in Oncology - Shreve, Paul.; Townsend, David W.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Clinical PET-CT in Radiology: Integrated Imaging in Oncology presents the latest hybrid scanning technology for applications of clinical PET-CT within body imaging. In this comprehensive text, Paul Shreve, MD, and David W. Townsend, PhD, have brought together an internationally-distinguished group of authors to cover all aspects of clinical PET-CT relevant to body oncology imaging technology using CT and FDG PET. The chapters provide practicing imaging physicians with a concise, practical guide, presenting PET-CT as an integrated anatomic-metabolic imaging procedure applied to cancer imaging. Physics and instrumentation chapters are oriented to provide an overview of the available technology and some physical concepts. Comprehensive clinical chapters are structured to provide concise and structured background regarding the clinical management of each cancer and the role of PET-CT imaging in all phases of patient management. Each clinical chapter will help the imaging physician more completely understand the relationship and role of the integrated modality imaging with respect to the overall treatment of the cancer patient.
Introduction -- PET-CT Physics -- PET-CT Scanning Protocols -- Patient Preparation and Practical Issues in PET-CT Scanning and Interpretation -- Principals of the Imaging Diagnosis and Staging of Cancer -- Principals of the Imaging Diagnosis of Cancer Response to Therapy -- PET-CT of Head and Neck Cancer -- PET-CT of Thoracic Malignancies -- PET-CT of Gastrointestinal Malignancies -- PET-CT of Genitourinary Malignancies -- PET-CT of Lymphoproliferative Disorders -- PET-CT of Melanoma -- PET-CT of Connective Tissue Malignancies and Osseous Metastatic Disease -- PET-CT of Breast Cancer.
Keywords: Medicine; Radiology, Medical; Nuclear medicine; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Nuclear Medicine